PENDIDIKAN KESEHATAN TENTANG DIABETES MELITUS PADA REMAJA MELALUI PENDEKATAN PEER EDUCATION - Zaenal Arifin; Harlina Putri Rusiana; Ilham Ilham; Baiq Rulli Fatmawati (Jurnal LENTERA, 2026)
Indonesia continues to face a double burden of disease, characterized by the persistence of infectious diseases alongside a rising prevalence of non-communicable diseases (NCDs). Among these, diabetes mellitus represents an increasing global health threat. Type 2 diabetes is the most common form, affecting both productive age groups and the elderly. The risk of developing diabetes in adolescents is exacerbated by the rising prevalence of cardiometabolic risk factors, including central obesity, elevated blood pressure, dyslipidemia, and glucose dysregulation. However, a peer-to-peer approach is needed to provide counseling regarding prevention because it has been proven effective in increasing knowledge and changing behavior. This community service activity aimed to enhance adolescents' knowledge and understanding of diabetes mellitus through health education. The methods employed included lectures followed by question-and-answer sessions conducted by nurse students as part of a peer group with the assistance of the community service team. Evaluations and observations conducted after the program demonstrated that the health education effectively improved the knowledge and understanding of adolescents at SMAN 7 Mataram regarding diabetes mellitus risk factors.